2018
DOI: 10.1002/hep.29802
|View full text |Cite
|
Sign up to set email alerts
|

Candidate biomarkers for the diagnosis and prognosis of drug‐induced liver injury: An international collaborative effort

Abstract: GLDH appears to be more useful than miR-122 in identifying DILI patients, and K18, OPN, and MCSFR are promising candidates for prediction of prognosis during an acute DILI event. Serial assessment of these biomarkers in large prospective studies will help further delineate their role in DILI diagnosis and management. (Hepatology 2018).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
223
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 194 publications
(242 citation statements)
references
References 41 publications
(47 reference statements)
14
223
5
Order By: Relevance
“…One cohort of healthy volunteers (Cohort 1) had three serial serum collections taken over 3 weeks, thus allowing for the calculation of intra‐individual variability. In agreement with previously reported data, the reference interval for GLDH was found to be ~1 to 10 U/L . The percentage coefficient of variation (%CV) is a measure of variability in the data.…”
Section: Promising New Dili Biomarkerssupporting
confidence: 91%
See 3 more Smart Citations
“…One cohort of healthy volunteers (Cohort 1) had three serial serum collections taken over 3 weeks, thus allowing for the calculation of intra‐individual variability. In agreement with previously reported data, the reference interval for GLDH was found to be ~1 to 10 U/L . The percentage coefficient of variation (%CV) is a measure of variability in the data.…”
Section: Promising New Dili Biomarkerssupporting
confidence: 91%
“…In agreement, various studies have demonstrated that patients with an acetaminophen overdose experience significant GLDH elevations . Similar to miR‐122, in acetaminophen overdoses GLDH appears to be more sensitive to liver injury than ALT and GLDH elevations also occur in idiosyncratic DILI …”
Section: Promising New Dili Biomarkerssupporting
confidence: 63%
See 2 more Smart Citations
“…Novel biomarkers, including HMBG1, have been proposed to be danger signals that can be measured in serum, and various cytokines, microRNAs, and acetylated HMGB1 have been proposed as serum biomarkers of immune cell activation . Identification of new and mechanistic biomarkers of drug‐induced liver injury has been a major focus of international research efforts, including a major new effort to start in 2019 . Mechanistic modeling incorporating production and release kinetics of these new biomarkers could make it possible to identify serious liver safety liability of new drug candidates early in clinical trials and with minimum subject risk and thus reducing the current need for large clinical trials to define liver safety.…”
mentioning
confidence: 99%